Turkey's Engagement with the African Organisations: Partner or Competitor?. (December 2020) - Sıradag˘, Abdurrahim
Turkey has been among one of the most active players in African politics over the last decade. The ruling Justice and Development Party (AK Party) governments have changed the traditional foreign policy approach towards Africa. Turkey has sought to develop its strategic relations with non-Western regional and sub-regional organisations during the AK Party governments. In this regard, Turkish Embassy in Addis Ababa was accredited to the African Union (AU) and other sub-regional African organisations since 2005. In this research, the main question is 'why has Turkey deepened and widened its strategic relations with African regional and sub-regional organizations?' This research will scrutinise Turkey's engagement with the African organisations by employing a theoretical approach and a holistic approach. According to the findings of this research, Turkey has changed its traditional approach towards African politics and played a dynamic role in establishing a new global order despite persistent challenges in the world.